ANALISIS LATAR SEBAGAI ATMOSFER DALAM CERPEN ”AKU PRIMADONA” KARYA YATTI SADELI - Oktapiani, Anisa; Lestari, Riana Dwi; Rosi, Rosi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The purpose of this study is to (1) analyze the background in the short story "I Primadona", and (2) describe the court as the atmosphere in the short story "Aku Primadona". Technically, the analysis is qualitative descriptive, with the following research steps: (1) reading the short story "Aku Primadona", (2) analyzing the background of the short story, and (3) describing the court as the atmosphere in the short story "Aku Primadona". The results of the analysis show that Yatti Sadeli created the setting as the atmosphere of my character, the Primadonna, who experienced the ups and downs of feelings in his life. The condition is not far from the human tidal life atmosphere.